2018
DOI: 10.1002/adma.201803716
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Magnetoelectric Composites with a Large Room‐Temperature Magnetoelectric Response through Molecular–Ionic Ferroelectrics

Abstract: Magnetoelectric materials with a large magnetoelectric response, a low operating magnetic (or electric) field, and a room‐temperature (or higher) operating temperature are of key importance for practical applications. However, such materials are extremely rare because a large magnetoelectric response often requires strong coupling between spins and electric dipoles. Herein, an example of a magnetoelectric composite is prepared by using a room‐temperature multiaxial molecular–ionic ferroelectric, tetramethylamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…As demonstrated previously that the ferroelectricity of [N(CH 3 ) 4 ][GaCl 4 ] originates from the displacement between the anion and cation, the enhancement in polarization of 1 is thus attributed to the dipole moment of the [GaBrCl 3 ] − anion itself ( μ = 1.667 Debye; based on the MP2/6‐311+G(d,p) calculations; Figure b) [6a,7]. Indeed, when the dipole moment of [GaBr 3 Cl] − anion was not considered, the calculated polarization value of 1 is the same as that of [N(CH 3 ) 4 ][GaCl 4 ] (4.37 μC cm −2 , Figure c and Table S3, Supporting Information) …”
supporting
confidence: 55%
See 4 more Smart Citations
“…As demonstrated previously that the ferroelectricity of [N(CH 3 ) 4 ][GaCl 4 ] originates from the displacement between the anion and cation, the enhancement in polarization of 1 is thus attributed to the dipole moment of the [GaBrCl 3 ] − anion itself ( μ = 1.667 Debye; based on the MP2/6‐311+G(d,p) calculations; Figure b) [6a,7]. Indeed, when the dipole moment of [GaBr 3 Cl] − anion was not considered, the calculated polarization value of 1 is the same as that of [N(CH 3 ) 4 ][GaCl 4 ] (4.37 μC cm −2 , Figure c and Table S3, Supporting Information) …”
supporting
confidence: 55%
“…The ratio of Br to Cl in 1 was determined by energy‐dispersive X‐ray spectroscopy (EDX), which indicated that the ratio of Br to Cl was 1:3 (Table S1, Supporting Information). The powder X‐ray diffraction (PXRD) measurement of 1 showed that its PXRD peaks were very similar to those observed in the ferroelectric [N(CH 3 ) 4 ][GaCl 4 ] (Figure a), suggesting that 1 probably crystallizes in the polar Amm 2 space group and may be a room‐temperature ferroelectric. Consistently, the single‐crystal determination demonstrated that 1 indeed crystallizes in the Amm 2 space group (Figure S1 and Table S2, Supporting Information).…”
mentioning
confidence: 73%
See 3 more Smart Citations